Pengembangan Model Manajemen Layanan Informasi Karir Berbasis ICT Bagi Peserta Didik SMA - Yohanes Andang Darmawan; Yari Dwikurnaningsih (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Research problem formulation is how to develop career information services in high school to improve high school students' understanding of careers. Research Objectives include: (1) knowing career information services that have been carried out in high school; (2) describes the advantages and disadvantages of career information services in high school; (3) developing ICT-based career information service models for high school students. The research was designed based on the objectives to be achieved, the approach used to use the method of